Building Block Converter Module for Universal (AC-DC, DC-AC, DC-DC) Fully Modular Power Conversion Architecture - Krishnamurthy, H.K.; Ayyanar, R. (2007 IEEE Power Electronics Specialists Conference, 2007)
This paper presents the configuration and control methods for a building block module suitable for application in a fully modular, AC-DC, DC-AC and DC-DC power conversion architecture, where the modules can be connected in any combination of series and parallel connections and support bidirectional power flow. The advantages of the proposed configuration, which is a combination of AC PWM full bridge stage and a dual active bridge based isolated DC-DC stage, are explained. The control implementations and average models of the building block module are discussed in detail. Analytical, simulation and experimental results are presented that confirm the feasibility of the fully modular power conversion approach with the proposed building block module.